New species, new synonyms, and resurrected taxa: A review of West and Central Palaearctic members of the genus Pseudoanthidium (Apoidea: Megachilidae) - Kasparek, Max (Zootaxa, 2024)
Wool carder bees of the genus Pseudoanthidium comprise approximately 60–65 species, which are found in the Palaearctic, Indo-Malayan and Afrotropical realms. Their taxonomic relationships are little understood. Herein, I revised West and Central Palaearctic members of the genus. Four species are described as new, namely P. farsiense sp. nov. from Iran, P. microrubrum sp. nov. from Morocco, P. syriacum sp. nov. from Syria, and P. tajikistanicum sp. nov. from Tajikistan. The largely overlooked species Anthidium fulviventre Friese, 1917, described from Russia, and Anthidium ivanovi Mavromoustakis, 1954, described from Tajikistan, are recognized as members of the Pseudoanthidium genus, as P. fulviventre (Friese, 1917) comb. nov. and P. ivanovi (Mavromoustakis, 1954) stat. resurrect. & comb. nov. Anthidium moricei Friese, 1911, from Jordan, and A. royoi Dusmet, 1915, from Morocco, are resurrected from synonymy with P. melanurum and suggested to be treated as P. moricei (Friese, 1911) stat. resurrect. and P. royoi (Dusmet, 1915) stat. resurrect. & comb. nov. The hitherto unknown males of P. moricei (Friese, 1911) and P. rubellulum Pasteels, 1969 are described based on material from Jordan and Israel, respectively. Royanthidium bicoloripenne Pasteels, 1981 (syn. nov.) from Morocco, is revealed to be a junior synonym of P. octodentatum (Pérez, 1895). Morphological traits, along with DNA sequences of the mitochondrial COI gene (“barcoding gene”), allowed clustering the species in five polytypic and five monotypic species groups. As key character traits of the type species of nominate Pseudoanthidium largely fit the subgeneric characters of the subgenus Royanthidium Pasteels, 1969, Royanthidium is regarded as a junior synonym (syn. nov.) of nominate Pseudoanthidium. The species of the subgenus Exanthidium Pasteels, 1969 form a uniform clade both in terms of morphology and DNA marker. An examination of the non-Palaearctic Pseudoanthidium species is suggested to determine whether Exanthidium deserves subgenus status.